The role of early social play behaviors and language skills for shy children’s later internalizing difficulties in school - Baardstu, Silje; Sette, Stefania; Brandlistuen, Ragnhild Eek; Wang, Mari Vaage (Frontiers in Psychiatry, 2023)
This longitudinal study explored the role of early social play behaviors and language skills in the associations between childhood shyness and later internalizing and language difficulties in school. Participants were N = 7447 children (50.1 % girls) from the Norwegian Mother, Father, and Child Cohort Study (MoBa). Latent direct, indirect, and interaction path analyses were performed within a structural equation framework. Results showed that mother-rated childhood shyness from age 18 months to age five years was associated with mother-rated internalizing difficulties and language problems at age eight years. Lower levels of teacher-reported social play behaviors and poorer language skills in preschool increased the risk of later anxiety problems among shy children, whereas higher levels of language competencies and social play behaviors buffered against later anxiety problems. The study identifies some of the early risk and protective factors that may influence shy children’s socio-emotional functioning and adjustment.